Model Business to Costumer (B2C) E-Commerce PT Indo Fira Global dalam Perspektif Ekonomi Syariah - Kuswanto, Welly (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2022)
This study aims to determine the business relations implemented by PT Indo Fira Global in the information system of book sales and online try outs. Development of an information system for book sales and online try outs implemented by PT Indo Fira Global based on PHP and MySQL (Case Study of PT Indo Fira) in a structured manner through the stages of system analysis, system design, implementation and system testing. System analysis is a researcher's analysis of weakness analysis, user needs, and data. System design is the researcher's analysis of sales system use cases, activity diagrams, and data flow diagrams. Implementation is writing program code in the application. While system trials are carried out to determine the function of the website created. Then the researcher took information from primary data sources and secondary data to find out the development of the B2C system that has been implemented by PT IndoFira Global. The results of program development show that book sales and online try outs based on PHP and MySQL carried out by PT Inddo Fira Global are not yet 100% sharia compliant. Therefore, PT Indo Fira Global is improving the management and revitalization of sharia-based sales to enhance the development of the Islamic economy in Indonesia.